Sex differences in the impact of parental obesity on offspring cardiac SIRT3 expression, mitochondrial efficiency, and diastolic function early in life - do Carmo, Jussara M.; Omoto, Ana C. M.; Dai, Xuemei; Moak, Sydney P.; Mega, Gabriela S.; Li, Xuan; Wang, Zhen; Mouton, Alan J.; Hall, John E.; da Silva, Alexandre A. (American journal of physiology. Heart and circulatory physiology, 2021)
Parental obesity contributes to diastolic dysfunction in young offspring (1–3 days after weaning) in a sex-dependent manner, as well as reduced cardiac SIRT3 expression and altered mitochondrial bioenergetics, resting Ca 2+ levels, and reduced phospholamban protein levels. Previous studies suggest that parental obesity may adversely impact long-term metabolic health of the offspring. We tested the hypothesis that parental (paternal + maternal) obesity impairs cardiac function in the offspring early in life. Within 1–3 days after weaning, offspring from obese rats fed a high-fat diet (HFD-Offs) and age-matched offspring from lean rats (ND-Offs) were submitted to echocardiography and cardiac catheterization for assessment of pressure-volume relationships. Then, hearts were digested and isolated cardiomyocytes were used to determine contractile function, calcium transients, proteins related to calcium signaling, and mitochondrial bioenergetics. Female and male HFD-Offs were heavier (72 ± 2 and 61 ± 4 g vs. 57 ± 2 and 49 ± 1 g), hyperglycemic (112 ± 8 and 115 ± 12 mg/dL vs. 92 ± 10 and 96 ± 8 mg/dL) with higher plasma insulin and leptin concentrations compared with female and male ND-Offs. When compared with male controls, male HFD-Offs exhibited similar systolic function but impaired diastolic function as indicated by increased IVRT (22 ± 1 vs. 17 ± 1 ms), E/E′ ratio (29 ± 2 vs. 23 ± 1), and tau (5.7 ± 0.2 vs. 4.8 ± 0.2). The impaired diastolic function was associated with reduced resting free Ca 2+ levels and phospholamban protein expression, increased activated matrix metalloproteinase 2, and reduced SIRT3 protein expression, mitochondrial ATP reserve, and ATP-linked respiration. These results indicate that male and female Offs from obese parents have multiple metabolic abnormalities early in life (1–3 days after weaning) and that male, but not female, Offs have impaired diastolic function as well as reductions in cardiac SIRT3, resting free Ca 2+ levels, and mitochondrial biogenesis. NEW & NOTEWORTHY Parental obesity contributes to diastolic dysfunction in young offspring (1–3 days after weaning) in a sex-dependent manner, as well as reduced cardiac SIRT3 expression and altered mitochondrial bioenergetics, resting Ca 2+ levels, and reduced phospholamban protein levels.